A co-simulation approach for heavy haul long distance locomotive-track simulation studies. Issue 9 (2nd September 2019) - Spiryagin, Maksym; Persson, Ingemar; Wu, Qing; Bosomworth, Christopher; Wolfs, Peter; Cole, Colin
ABSTRACT: The operation of heavy haul high adhesion locomotives on the long distance track from mines to ports is a subject of recent track damage studies. Such studies require the introduction of a traction power system for each locomotive running in the heavy haul train followed by consideration of the whole system developed as a complex mechatronic model. It is nowadays common to use co-simulation for the creation of mechatronic models. This paper introduces an approach which can be applicable for a whole train simulation and is based on the combination of two types of software – a multibody simulation package for the mechanical model of a heavy haul locomotive and tools for simulation of traction power systems. This paper describes the integration of a shared library, generated by means of Simulink Code Generation, in Gensys multibody software for the co-simulation process. The validation of the newly developed approach has been performed by means of the simulation of both simplified and full traction control systems for a heavy haul locomotive running on straight track with the same scenarios previously used for the existing co-simulation approach based on a TCP/IP data exchange interface. Validation of the newly developed approach has also been performed with longitudinal train dynamics considered.